Best Answer

This quadratic expression cannot be factored because its discriminant is less than zero

Q: 3x squared minus 3x plus 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(3x-2)(x-2)

(x + 3)(3x - 2)

3x2+x-2 = (3x-2)(x+1) when factored

2(5x - 1)(3x - 2)

(x - 2)(2x + 7)

Related questions

x^2 + 3x + 2/(-3x) - x^2 - 2=3x-2+2/(-3x)=3x-2-2/(3x)

(3x-2)(x-2)

(x + 3)(3x - 2)

(x + 2)(3x - 1)(3x + 1)

3x2+x-2 = (3x-2)(x+1) when factored

3x^2 -14x +15 = (3x-5)(x-3)

9x2 - 6xy + y2 - 81 = (3x - y)2 - 92 = (3x - y - 9)(3x - y + 9)

2(5x - 1)(3x - 2)

The factors are [3x + 5 - 2*sqrt(10)] and [3x 5 + 2*sqrt(10)].

(x - 2)(2x + 7)

9x2 - 6xy + y2 - 81 = (3x - y)2 - 81 = (3x - y - 9)*(3x - y + 9)

3x^2+3x-60=3(x^2+x+20)=3(x+5)(x-4)